A Review of the Pharmacological Properties of Psoralen - Ren, Yali; Song, Xiaominting; Tan, Lu; Guo, Chuanjie; Wang, Miao; Liu, Hui; Cao, Zhixing; Li, Yuzhi; Peng, Cheng (Frontiers in Pharmacology, 2020)
Psoralen is the principal bioactive component in the dried fruits of Psoralea corylifolia L. termed “Buguzhi” in traditional Chinese medicine(TCM). Recent studies have demonstrated that psoralen displays multiple bioactive properties, beneficial for the treatment of osteoporosis, tumors, viruses, bacteria, and inflammation. The present review focuses on the research evidence relating to the properties of psoralen gathered over recent years. Firstly, multiple studies have demonstrated that psoralen exerts strong anti-osteoporotic effects via regulation of osteoblast/osteoclast/chondrocyte differentiation or activation due to the participation in multiple molecular mechanisms of wnt/β-catenin, bone morphogenetic protein （BMP）, inositol-requiring enzyme 1 (IRE1) / apoptosis signaling kinase 1 (ASK1）/ c-jun N-terminal kinase (JNK) and the Protein Kinase B(AKT) / activator protein-1 (AP-1) axis, and the expression of miR-488, peroxisome proliferators-activated receptor-gamma (PPARγ), and matrix metalloproteinases (MMPs). In addition, the antitumor properties of psoralen are associated with the induction of ER stress-related cell death via enhancement of PERK: Pancreatic Endoplasmic Reticulum Kinase (PERK)/activating transcription factor (ATF), glucose-regulated protein of 78 (GRP78) / C/EBP homologous protein (CHOP) and glucose-regulated protein of 94 (GRP94)/CHOP signaling, and inhibition of P-glycoprotein (P-gp) or ATPase that overcomes multidrug resistance. Furthermore, multiple articles have shown that the antibacterial, anti-inflammatory and neuroprotective effects of psoralen are a result of its interaction with viral polymerase (Pol), destroying the formation of biofilm, and regulating the activation of tumor necrosis factor alpha (TNF-α), transforming growth factor beta (TGF-β), interleukin 4/5/6/8/12/13 (IL-4/5/6/8/12/13), GATA-3, acetylcholinesterase (AChE), and the hypothalamic-pituitary-adrenal (HPA) axis. Finally, the toxic effects and mechanisms of action of psoralen have also been reviewed.